Multivariate time‐dependent comparison of the impact of lenalidomide in lower‐risk myelodysplastic syndromes with chromosome 5q deletion. (10th April 2014) - Sánchez‐García, Joaquín; del Cañizo, Consuelo; Lorenzo, Ignacio; Nomdedeu, Benet; Luño, Elisa; de Paz, Raquel; Xicoy, Blanca; Valcárcel, David; Brunet, Salut; Marco‐Betes, Victor; García‐Pintos, Marta; Osorio, Santiago; et al.
Summary: The impact of lenalidomide treatment on long‐term outcomes of patients with lower risk myelodysplastic syndromes (MDS) and chromosome 5q deletion (del(5q)) is unclear. This study used time‐dependent multivariate methodology to analyse the influence of lenalidomide therapy on overall survival (OS) and acute myeloblastic leukaemia (AML) progression in 215 patients with International Prognostic Scoring System (IPSS) low or intermediate‐1 risk and del(5q). There were significant differences in several relevant characteristics at presentation between patients receiving ( n  = 86) or not receiving lenalidomide ( n  = 129). The 5‐year time‐dependent probabilities of OS and progression to AML were 62% and 31% for patients receiving lenalidomide and 42% and 25% for patients not receiving lenalidomide; differences were not statistically significant in multivariate analysis that included all variables independently associated with those outcomes (OS, P  =   0·45; risk of AML, P  =   0·31, respectively). Achievement of RBC transfusion independency ( P  =   0·069) or cytogenetic response ( P  =   0·021) after lenalidomide was associated with longer OS in multivariate analysis. These data clearly show that response to lenalidomide results in a substantial clinical benefit in lower risk MDS patients with del(5q). Lenalidomide treatment does not appear to increase AML risk in this population of patients.